Menelaah kembali perilaku belanja makanan online di era pandemi covid-19 - Rio Satria Nugroho (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2021)
The COVID-19 pandemic has changed the social order of human life, public health, and business operations with so many social restrictions that occur. The phenomenon has changed food shopping behaviour in society. This article aims to analyze changes in food shopping due to the limited space for human mobility and cause all aspects of life to depend on internet technology in Indonesia. Online food delivery platforms or Mobile Food Ordering Applications (MFOA) provide an accessible marketplace for any restaurant which is significantly utilized during the pandemic era. Online food delivery services also carry out advertising activities through internet marketing. The method used in this article is a literature review. The results show that this change in spending patterns is supported by many official policies to stay at home. Advertising messages with content showing sympathy and solidarity are the most sought after by consumers in the pandemic era. The implications of this research can be initial research to conduct more in-depth research in terms of consumer behaviour, internet marketing, and advertising in the context of digital media during the pandemic. Understanding the consumer landscape will enable online food delivery platforms to fulfill their full potential in terms of impacting people's economies, businesses, and quality of life.